Illegal action - Rimington, Stella (London : Hutchinson, 2007)
In her new assignment, MI5 officer Liz Carlyle uncovers a plot to silence Nikita Brunovsky, an increasingly vocal opponent of Vladimir Putin. The Foreign Office is adamant about forestalling a crime that could become a full-blown international incident, but there's not a single clue as to how the assassination will be carried out--and Liz is solely responsible for averting disaster. So she goes undercover, attaching herself to Brunovsky's retinue: racing against the clock to determine who betrayed him and suddenly facing a wholly unexpected second task--unmasking a Russian operative working undercover alongside her--From publisher description.
Keywords: Women intelligence officers -- Fiction; Detective and mystery fiction